Effect of zinc supplementation on diarrhoea in HIV infection: a protocol for systematic review and meta-analysis of controlled clinical trials - Chang Liu; Jiyuan Shi; Peiling Li; Panpan Guo; Shitong Guo; Shujing Suo (BMJ Open)
Introduction Diarrhoea is a common problem in people living with HIV. Some trials have demonstrated the effectiveness of zinc supplementation in the prevention and treatment of diarrhoea; however, several studies employing the effectiveness of zinc supplementation for reducing diarrhoea in HIV infection have reported heterogeneous outcomes, necessitating a systematic review to provide an exhaustive summary of current evidence. This review aims to pool the available evidence on the effectiveness of zinc supplementation on diarrhoea in HIV infection.Methods and analysis This systematic review protocol follows the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols. A systematic literature search will be conducted in Chinese and English databases, including PubMed, Scopus, Google Scholar, Cochrane Library, EMBASE, Web of Science, China National Knowledge Infrastructure, Chinese Scientific Journal Database, SinoMed and Wanfang, as part of our search strategy from inception to 17 May 2025. Two reviewers will independently identify eligible studies and extract data. The risk of bias in included studies will be assessed using version 2 of the Cochrane risk-of-bias tool for randomised trials. The risk ratio and 95% CIs will be used to estimate the efficacy of treatment and evaluation approach to rate the certainty of evidence. Cochran’s Q and the I2 will be used to evaluate statistical heterogeneity. Data will be analysed using Stata version 13.0.Ethics and dissemination Because no patients were involved, ethical approval was not required. The final results of this research will be submitted to a peer-reviewed journal or presented at relevant conferences, and any deviations from this protocol will be recorded and explained in the final report.PROSPERO registration number CRD42022328098.